Selection of Effective Therapies Using Three-Dimensional in vitro Modeling of Chondrosarcoma - Palubeckaitė, Ieva; Venneker, Sanne; Briaire-de Bruijn, Inge H.; van den Akker, Brendy E.; Krol, Augustinus D.; Gelderblom, Hans; Bovée, Judith V. M. G. (Frontiers in Molecular Biosciences, 2020)
Chondrosarcomas are a group of cartilaginous malignant neoplasms characterized by the deposition of chondrogenic extracellular matrix. Surgical resection is currently the only curative treatment option, due to their high resistance to conventional chemotherapy and radiotherapy. Novel therapeutic treatment options may improve outcome. Predominantly used cell line monolayer in vitro models lack in vivo complexity, such as the presence of extracellular matrix, and differing oxygen access. Hence, we aimed to improve pre-clinical chondrosarcoma research by developing an alginate-based 3D cell culture model. An alginate scaffold was applied to generate spheroids of three chondrosarcoma cell lines (CH2879, JJ012, SW1353). Morphological, histological and immunohistochemical assessment of the spheroids were used to characterize the chondrosarcoma model. Presto blue assay, morphological and immunohistochemical assessment were applied to assess spheroid response to a panel of chemotherapeutics and targeted therapies, which was compared to conventional 2D monolayer models. Synergistic effect of doxorubicin and ABT-737 (Bcl-2 inhibitor) was compared between monolayer and spheroid models using excess over Bliss. A 3D colony formation assay was developed for assessment of radiotherapy response. Chondrosarcoma spheroids produced chondrogenic matrix and remained proliferative after two weeks of culture. When treated with chemotherapeutics, the spheroids were more resistant than their monolayer counterparts, in line with animal models and clinical data. Moreover, for sapanisertib (mTOR inhibitor) treatment, a recovery in chondrosarcoma growth, previously observed in mice models, was also observed using long-term treatment. Morphological assessment was useful in the case of YM-155 (survivin inhibitor) treatment where a fraction of the spheroids underwent cell death, however a large fraction remained proliferative and unaffected. Synergy was less pronounced in 3D compared to 2D. A 3D clonogenic assay confirmed increased resistance to radiotherapy in 3D chondrosarcoma spheroids. We demonstrate that the chondrosarcoma alginate spheroid model is more representative of chondrosarcoma in vivo and should be used instead of the monolayer model for therapy testing. Improved selection at in vitro stage of therapeutic testing will increase the amount of information available for experimental design of in vivo animal testing and later, clinical stages. This can potentially lead to increased likelihood of approval and success at clinical trials.